Environmental Archaeology Current Theoretical and Methodological Approaches (Interdisciplinary Contributions to Archaeology,, 2018)
This book aims to thoroughly discuss new directions of thinking in the arena of environmental archaeology and test them by presenting new practical applications. Recent theoretical and epistemological advancement in the field of archaeology calls for a re-definition of the subdiscipline of environmental archaeology and its position within the practise of archaeology. New technological and methodological discoveries in hard sciences and computer applications opened fresh ways for interdisciplinary collaborations thus introducing new branches and specialisations that need now to be accommodated and integrated within the previous status-quo. This edited volume will take the challenge and engage with contemporary international discussions about the role of the discipline within the general framework of archaeology. By drawing upon these debates, the contributors to this volume will rethink what environmental archaeology is and what kind of input the investigation of this kind of materiality has to the reconstruction of human history and sociality. .